2013
DOI: 10.1128/aac.00252-13
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Salt Resistance of Short Antimicrobial Peptides

Abstract: bThe efficacies of many antimicrobial peptides are greatly reduced under high salt concentrations, therefore limiting their use as pharmaceutical agents. Here, we describe a strategy to boost salt resistance and serum stability of short antimicrobial peptides by adding the nonnatural bulky amino acid ␤-naphthylalanine to their termini. The activities of the short salt-sensitive tryptophan-rich peptide S1 were diminished at high salt concentrations, whereas the activities of its ␤-naphthylalanine end-tagged var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 25 publications
2
92
1
1
Order By: Relevance
“…Our data indicated that A-hBD-2 has stronger anti-S. aureus activity under various concentrations (50 μg/mL, 70 μg/mL, and 100 μg/mL) compared with hBD-2. Natural AMPs lose their antimicrobial activity at physiological salt concentrations, thereby limiting their potential clinical application [16]. Our study found that both hBD-2 and A-hBD-2 had lower antibacterial abilities with increased NaCl concentrations.…”
Section: Discussionmentioning
confidence: 74%
“…Our data indicated that A-hBD-2 has stronger anti-S. aureus activity under various concentrations (50 μg/mL, 70 μg/mL, and 100 μg/mL) compared with hBD-2. Natural AMPs lose their antimicrobial activity at physiological salt concentrations, thereby limiting their potential clinical application [16]. Our study found that both hBD-2 and A-hBD-2 had lower antibacterial abilities with increased NaCl concentrations.…”
Section: Discussionmentioning
confidence: 74%
“…Serum inactivates peptides either through cleavage by proteases or through binding with proteins or lipids (30) We observed that RRIKA but not RR retained its bactericidal activity, although at a lower rate, in the presence of 10% FBS. Furthermore, both RRIKA and RR retained their antibacterial activity when tested in increasing concentration of NaCl and MgCl 2 , in contrast to many well-studied AMPs (such as LL-37, human ␤-defensin-1, gramicidins, bactenecins, and magainins) which showed substantially reduced antibacterial activities under the same conditions (11). Previously, Turner et al reported that LL-37 and human neutrophil peptide-1 (HNP-1) demonstrated 12-fold and 100-fold increases in the MIC of MRSA, respectively, when 100 mM NaCl was added to the test medium (10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their production cost is high (8,9). In addition, many natural AMPs lose their antimicrobial activity in physiological salt concentrations (10,11). These characteristics have substantially hindered their pharmaceutical development as new therapeutic agents.…”
mentioning
confidence: 99%
“…After incubation at 37°C for 2, 4, 6, or 8 h, the remaining amount of peptides was determined by reverse-phase HPLC [34]. All stability tests in serum, saliva, BHI medium and PBS were repeated three times.…”
Section: Nal-p-113 Stability Testmentioning
confidence: 99%